The effects of climate change on high elevation lake ecosystems - Christianson, Kyle R., author; Johnson, Brett, advisor; Hooten, Mevin, committee member; Denning, Scott, committee member; Myrick, Christopher, committee member (Colorado State University. Libraries, 2019)
High elevation lakes are an important class of the world's fresh water. Nearly 10% of all lakes globally reside above 2,100 m ASL and almost half of the world's population relies on water from high elevation regions. Also, these lakes provide important cool water habitat refugia for aquatic biota. However, high elevation areas are sensitive to changes in climate and are changing faster than other regions. Likewise, secondary effects of a changing climate like drought, forest fire, and eutrophication threaten lake habitats, exacerbating changes from air warming. Despite the importance of high elevation lakes and their increased threat from climate change, little is known about high elevation lakes and their vulnerability to these threats. The goal of my dissertation was first (Chapter 1) to determine historic changes in lake surface temperatures for a set of high elevation lakes in the Southern Rocky Mountains, USA (SRM). Then, I determined potential future changes to thermal stratification (Chapter 2) and the length of the open water season (Chapter 3) for a subset of lakes in the Rawah Wilderness Area (RWA) within the SRM. For these future predictions, I estimated alterations in lake surface and bottom temperatures from multiple stressors, as well as how these changes may affect aquatic habitat for native and nonnative fish species that reside in the region. Although historic lake temperature trend analyses are numerous, remote lakes, including many high elevation lakes, are typically underrepresented due to limited availability of long-term datasets. In Chapter 1, I developed a Bayesian modeling technique to analyze sparse data from high elevation lakes that allowed me to estimate lake surface warming across a large region (SRM). The analysis allowed for inclusion of lakes with few repeated measurements, and observations made prior to 1980 when more intensive lake monitoring began. I accumulated the largest dataset of high elevation lake surface temperatures globally analyzed to date. Data from 590 high elevation lakes in the Southern Rocky Mountains showed a 0.13°C decade-1 increase in surface temperatures and a 14% increase in seasonal degree days since 1955. Like surface temperature trends, many studies have also examined the effects of climate warming on lake thermal stratification, but few have addressed environmental changes concomitant with climate change, such as alterations in water clarity and lake inflow. Although air temperature rise is a predominant factor linked to lake thermal characteristics, climate-driven changes at watershed scales can substantially alter lake clarity and inflow, exacerbating the effects of future air warming on lake thermal conditions. In Chapter 2, I employed the mechanistic General Lake Model (GLM) to simulate future thermal conditions of typical mountain lakes of the western United States. I found that after air temperature, alterations in inflow had the largest effect on lake thermal conditions, changes in wind had the least effect, and large lakes experienced more than double the increase in lake stability than small lakes. Assuming air temperature rise alone, summer stability of mountain lakes of the western United States was predicted to increase by 15-23% at +2°C air temperatures, and by 39-62% at +5°C air temperatures. When accounting for associated changes in clarity and inflow, lake stability was predicted to increase by 208% with +2°C air warming and 318% at +5°C air warming. Finally, the open water duration at high elevations is increasing at a higher rate than at lower elevations. Earlier snowmelt, resulting in decreased ice cover duration, is having a proportionally higher effect on mountain lakes than other regions. But the effect early melt and increased air temperatures have on mountain lake thermal characteristics and implications for fish is unclear. Mountain lakes exhibit a variety of thermal conditions, altering metabolic requirements for ectotherms. In Chapter 3, I coupled GLM with a fish bioenergetics model to assess potential thermal changes and energetic consequences for native Cutthroat Trout (Oncorhynchus clarkii spp.) and nonnative but present Brook Trout (Salvelinus fontinalis) in a continuously mixed polymictic and seasonally stratified dimictic mountain lake during early and nominal snowpack melt in the SRM. I found that early snowmelt alone had a larger consumptive demand for all species than an air temperature increase of 2°C, but combined these environmental changes are most effective. Early melt coupled with 5°C air warming could more than double the food requirements for Cutthroat Trout and Brook Trout. Ultimately, food availability may dictate the future success of fish in mountain regions. My dissertation research expanded the current knowledge of high elevation lake thermal conditions, developed a novel method to utilize sparse datasets, and provided valuable holistic insight to potential future changes in lake thermal structure and habitat suitability for fish while accounting for localized and watershed scale consequences of climate change.